Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.idcr.2020.e00973
|View full text |Cite
|
Sign up to set email alerts
|

Cavitary pulmonary tuberculosis with COVID-19 coinfection

Abstract: The COVID-19 pandemic has strained the healthcare system worldwide, leading to an approach favoring judicious resource allocation. A focus on resource preservation can result in anchoring bias and missed concurrent diagnosis. Coinfection of Mycobacterium tuberculosis (TB) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has implications beyond morbidity at the individual level and can lead to unintended TB exposure to others. We present six cases of COVID-19 with newly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 10 publications
(10 reference statements)
0
25
0
3
Order By: Relevance
“…Another review indicated that the prevalence of co-infection among COVID-19 patients varied; however, it could be up to 50% among non-survivors [31] . At present, many microorganisms have been reported as the co-pathogens, including S. pneumoniae, S. aureus, K. pneumoniae, Mycoplasma pneumoniae, Chlamydophila pneumoniae, Legionella pneumophila, E. coli, P. aeruginosa, S. maltophilia, A. baumannii and Mycobacterium tuberculosis; Candida and Aspergillus species; and viruses such as influenza, coronavirus, rhinovirus/enterovirus, para-influenza, metapneumovirus, influenza B virus, and human immunodeficiency virus [ 15 , 28 , 31 , 32 , 33 , 34 ]. However, the majority of MDROs developed in patients with severe or critical COVID-19 and the incidence of co- or secondary infection may increase, resulting in prolonged hospitalization [ 16 , 18 , 20 , 25 , 28 , 31 ].…”
Section: Variable Rate Of Co-infectionmentioning
confidence: 99%
“…Another review indicated that the prevalence of co-infection among COVID-19 patients varied; however, it could be up to 50% among non-survivors [31] . At present, many microorganisms have been reported as the co-pathogens, including S. pneumoniae, S. aureus, K. pneumoniae, Mycoplasma pneumoniae, Chlamydophila pneumoniae, Legionella pneumophila, E. coli, P. aeruginosa, S. maltophilia, A. baumannii and Mycobacterium tuberculosis; Candida and Aspergillus species; and viruses such as influenza, coronavirus, rhinovirus/enterovirus, para-influenza, metapneumovirus, influenza B virus, and human immunodeficiency virus [ 15 , 28 , 31 , 32 , 33 , 34 ]. However, the majority of MDROs developed in patients with severe or critical COVID-19 and the incidence of co- or secondary infection may increase, resulting in prolonged hospitalization [ 16 , 18 , 20 , 25 , 28 , 31 ].…”
Section: Variable Rate Of Co-infectionmentioning
confidence: 99%
“…A duração da hospitalização variou de 22 dias a 130 dias. Por fim, a letalidade variou entre 11,6% e 33,3% nos estudos com amostra maior que um paciente, com exceção de Yousaf et al (2020) Legenda: RT-PCR: Reverse-transcriptase polymerase chain reaction; BAAR: bacilo álcool ácido resistente; LCR: líquido cefalorraquidiano; VHS: velocidade de hemossedimentação; TP: tempo de protrombina; PTTa: tempo de tromboplastina parcial ativada; INR: razão de normatização internacional; ALT: alanina aminotransferase; AST: aspartato aminotransferase; LDH: desidrogenase láctica; TC: tomografia computadorizada; RX: raio X; RM: ressonância magnética; EEG: eletroencefalograma; I.V. : intravenosa; ADH: hormônio antidiurético.…”
Section: Resultsunclassified
“…Quando solicitados exames de imagem, o principal método utilizado foi a tomografia computadorizada (TC) de tórax que mostrou nos pacientes uma sobreposição geralmente bilateral de achados de ambas as condições, como a árvore em brotamento, cavidades ou consolidações da tuberculose com o padrão em vidro fosco ou espessamento intersticial do COVID-19 (Luciani et al 2020;Motta et al 2020;Sarinoglu et al 2020;Tham, et al 2020;Yao et al 2020). O raio X (RX) de tórax também apresentou achados de ambas as patologias, como cavitações, opacificações e derrame pleural (Ata et al 2020;Sarinoglu et al 2020;Tham, et al 2020;Yousaf et al 2020). Nenhum dos trabalhos analisou se o padrão de imagem da TC ou do RX de tórax dos pacientes coinfectados era mais grave que o de pacientes apenas com COVID-19.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, these four patients did have infection with bacterial organisms known to cause cavitation. Infection with mycobacterium tuberculosis (MTB) is also a common cause of lung cavitation and in a recently published case series [ 16 ], it has been described as a coinfection in COVID-19 patients resulting in cavity formation. However, in all 12 of our patients, MTB infection was ruled out based on negative Acid-Fast Bacilli on smear and culture of multiple respiratory specimens.…”
Section: Discussionmentioning
confidence: 99%